Chaotic Color Image Encryption Scheme Using Deoxyribonucleic Acid (DNA) Coding Calculations and Arithmetic over the Galois Field. (9th March 2020) - Huang, Lilian; Wang, Shiming; Xiang, Jianhong; Sun, Yi
Abstract : This paper proposes a chaotic color image encryption scheme based on DNA-coding calculations and arithmetic over the Galois field. Firstly, three modified one-dimensional (1D) chaotic maps with larger key space and better chaotic characteristics are presented. The experimental results show that their chaotic intervals are not only expanded to 0, 15, but their average largest Lyapunov Exponent reaches 10. They are utilized as initial keys. Secondly, DNA coding and calculations are applied in order to add more permutation of the cryptosystem. Ultimately, the numeration over the Galois field ensures the effect for the diffusion of pixels. The simulation analysis shows that the encryption scheme proposed in this paper has good encryption effect, and the numerical results verify that it has higher security than some of the latest cryptosystems.